Philosophy and Neuroscience A Methodological Analysis - Gouveia, Steven S. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book explores the methodological strategies for linking philosophy and neuroscience concerning the study of the conscious brain. The author focuses on four distinct methods for relating these two academic disciplines: isolationist, reductionist, neurophenomenological, and non-reductionist. After analyzing the pros and cons of these approaches, Steven S. Gouveia applies them to the concept of Qualia and Information to understand how the metaphilosophical assumptions of each approach influence the definitions of those specific concepts. Gouveia argues for an approach that conceives the interdisciplinarity of both philosophy and neuroscience, in a particular and sound methodology, offering empirical examples of the explanatory power of this methodology over the others. Additionally, he shows how the metaphilosophical assumptions of each methodology-usually taken by researchers implicitly and unconsciously-influence their own approach to the methodological problem. Steven S. Gouveia is a Post Doctoral Research Fellow at the Mind, Brain Imaging and Neuroethics Unit of the Royal Institute of Mental Health, University of Ottawa, Canada.
Chapter 1 - Methodological Problem in Philosophy and Neuroscience -- Chapter 2 - Methodological Isolationism -- Chapter 3 - Reductive Neurophilosophy -- Chapter 4 - Neurophenomenology -- Chapter 5 - Non-Reductive Neurophilosophy -- Chapter 6 - Qualia and Information in Philosophy and Neuroscience -- Conclusion.
Keywords: Philosophy of mind; Knowledge, Theory of; Cognitive neuroscience; Philosophy of Mind; Epistemology; Cognitive Neuroscience